Rate and extent of losses from top spoilage in alfalfa silages stored in bunker silos - D.L. Holthaus; Matthew A. Young; L. Pfaff; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1994)
Alfalfa silages were made in pilot- and farm-scale silos, and five sealing treatments were compared. After 90 days, sealing dramatically reduced dry matter (DM) losses at the 5 and 10 inch depths in the farm silos and at the 0 to 12, 12 to 24, and 24 to 36 inch depths in the pilot silos. Extending the storage period to 180 days in pilot silos had no effect on DM losses for sealed or delay-sealed silages, but DM losses for unsealed silages continued to increase at all three depths. Placing a roof over the unsealed, farm-scale silo increased the silage DM content at all three depths, increased storage temperatures at the 10 and 20 inch depths, and reduced DM loss at the 10 inch depth compared to the unsealed silo without a roof. Rainfall was much above normal (16.8 inches during the first 90 days of storage; 11.2 inches the second 90 days) and contributed to huge increases in the moisture content of silage at the lower depths in the unsealed, no roof, pilot- and farm-scale silos. Sealing also increased the nutritive value of the silages at the 5 and 10 inch depths.; Dairy Day, 1994, Kansas State University, Manhattan, KS, 1994;
Keywords: Dairy Day; 1994; Kansas Agricultural Experiment Station contribution; no. 95-141-S; Report of progress (Kansas Agricultural Experiment Station); 716; Silage; Alfalfa; Top spoilage; Bunker Silos